UPAYA MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE (STAD) - Rosmita, Rosmita; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThis study aimed to improve social studies learning outcomes by using cooperative type Student Team Achievement Devisions (STAD) in Eighth Grade at SMP Negeri 4 Teriak Bengkayang. The sub-problem in this study is "How do student learning outcomes by applying modelsÂ  Cooperative learning type Student Team Achievement Devisions (STAD)? How is the implementation of the cooperative learning model type Student Team Achievement Devisions (STAD) in social studies subjects Eight grade in SMP Negeri 4 Teriak? Is there an increase in social studies learning outcomes for VIII grade students in SMP Negeri 4 TeriakÂ  by applying the cooperative learning model type Student Team Achievement Devisions (STAD)?â€. The form of research used was classroom action research conducted for 2 cycles. Each cycle consists of four stages: action planning, action implementation, observation and reflection. The research method used in this research is descriptive method. The average post-test scores of cycle I and cycle II increased by 15.66.Â  Percentage of completeness.Â  The percentage of mastery learning in post-test cycle I and cycle II increased by 21.74%.Keywords: Cooperative Learning Model Type Student Team Achievement Devisions (STAD), Learning outcomes, Social studies